2008
DOI: 10.1177/1368430207084848
|View full text |Cite
|
Sign up to set email alerts
|

Relative Deprivation, Attitude Contrast Projection, and Opinion Certainty

Abstract: This research examines social projection between relatively deprived groups and its effect on opinion certainty. In Study 1, disadvantaged and advantaged group members indicated their own attitudes on six issues, and then estimated the positions either of their in-group, their respective rival out-group, a control out-group, or they received no opportunity to project. As expected, disadvantaged participants projected attitudinal contrast onto their advantaged rival out-group. Negative thoughts about the rival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The few examples of negative social projection were found among people who both strongly identified with their ingroup and perceived strong conflict with the outgroup (Riketta, 2005), among members of a low status group with regards to the perception of the attributes of the high status group (Holtz & Nihiser, 2008), and among people who perceive high social distance between their ingroup and the outgroup (Jones, 2004).…”
Section: Studymentioning
confidence: 95%
“…The few examples of negative social projection were found among people who both strongly identified with their ingroup and perceived strong conflict with the outgroup (Riketta, 2005), among members of a low status group with regards to the perception of the attributes of the high status group (Holtz & Nihiser, 2008), and among people who perceive high social distance between their ingroup and the outgroup (Jones, 2004).…”
Section: Studymentioning
confidence: 95%
“…Psychological research finds that evaluations of dissimilar others elicits a spontaneous self-evaluation and ironically solidifies our certainty about our own opinions and attitudes. In fact, certainty about our own preferences increases to the extent that the we perceive the target of our evaluation to be dissimilar to ourselves (Holtz and Miller, 2001; Holtz and Nihiser, 2008). In other words, this research suggests that rather than using the self as an anchor for evaluating other people (i.e., self-projection), the evaluation of other people triggers a spontaneous self-evaluation.…”
Section: A New Conceptualization Of the Role Of Mpfc In Social Cognitmentioning
confidence: 99%
“…However, if the attitudes of dissimilar others are clearly different, then the correctness of the attitude is verified in terms of social distinctiveness (Hogg and Mullin 1999) and uncertainty decreases (Holtz and Miller 2001). Indeed, Holtz and colleagues (Holtz 2003(Holtz , 2004Holtz and Miller 2001;Holtz and Nihiser 2008) found that the larger the perceived difference between the own attitude and that of dissimilar others, the less uncertain individuals are that their own attitudes are correct (see also Hensley and Duval 1976).…”
Section: Uncertainty As An Endogenous Factormentioning
confidence: 99%
“…For both mechanisms researchers have found empirical support. A number of experiments conducted by Holtz and colleagues (Holtz 1997(Holtz , 2003(Holtz , 2004Miller 1985, 2001;Holtz and Nihiser 2008) suggest that already mere subjective perception of consensual support for one's attitudes by similar others is connected to decreased uncertainty. This effect is stronger the more similar attitudes of these others are assumed to be (Holtz and Miller 2001;Holtz and Nihiser 2008), and the more important the specific issue is to the individual (e.g.…”
Section: Uncertainty As An Endogenous Factormentioning
confidence: 99%
See 1 more Smart Citation